Impacts of the Ways in the Local Community of Santiago de Compostela: Results of a Research Project in Progress - Samartim, Roberto; Pazos-Justo, Carlos (Madrygal. Revista de Estudios Gallegos, 2020)
We introduce an initial assessment (and critical reflection) of all the results linked to the research project “Speeches, images and cultural practices on Santiago de Compostela as a goal of the Paths” (FFI2012-35521), developed between 2011 and 2017 by a multidisciplinary and interuniversitary research team linked to the Galabra Network (https://redegalabra.org/).The research takes as a point of departure a set of publications resulting from representative analyzes carried out on sections of the general corpus of the project. This corpus is composed by a documentary archive of books, audiovisuals and websites, plus surveys and interviews to inhabitants, shopkeepers and visitors (from Galicia, Portugal, Spain and Brazil) between 2013 and 2015. The survey carried out on our first production on the project allows to conclude, among other issues, the validity of the methods and procedures of work by questionnaire or Natural Language Processing (NLP); the impact of Paulo Coelho on the practices of visitors (namely Brazilians); or even the centrality of the Catholic Church and religion in the comprehension of the Way and the city, along with the construction of an image of the city / community linked to spirituality and medievalism.